A two-stage Microgrid cost optimization considering distribution network loss and voltage deviation. (February 2020) - Gao, Jie; Chen, Jia-Jia; Cai, Ying; Zeng, Shun-Qi; Peng, Ke
Abstract: This paper proposes a novel two-stage Microgrid (MG) scheduling methodology to decide optimal location and size of MG and outputs of dispatchable and intermittent distributed generators (DGs). In the first stage, a system stability index (SSI) representing the performance of the distribution network is proposed to select the location of the MG. The size of the MG is derived by minimizing of SSI. In the second stage, the group search optimizer (GSO) algorithm is applied to further determine the outputs of each DG in the MG, including photovoltaic (PV) panels, wind turbines (WT), battery energy storage systems (BESS) and diesel generators (DIG). To validate the proposed approach, the IEEE 33-bus radial distribution systems has been applied. The simulation results show that the approach minimizes MG investment costs under the premise of considering loss and voltage deviation of the distribution network.